Immunotherapy (oral and sublingual) for food allergy to fruits (Review) (2015)
ABSTRACT: BackgroundFood allergy is an abnormal immunological response following exposure (usually ingestion) to a food. Elimination of the allergen is theprinciple treatment for food allergy, including allergy to fruit. Accidental ingestion of allergenic foods can result in severe anaphylacticreactions. Allergen-specific immunotherapy (SIT) is a specific treatment, when the avoidance of allergenic foods is problematic. Recently,studies have been conducted on different types of immunotherapy for the treatment of food allergy, including oral (OIT) and sublingualimmunotherapy (SLIT).ObjectivesTo determine the efficacy and safety of oral and sublingual immunotherapy in children and adults with food allergy to fruits, whencompared with placebo or an elimination strategy.Search methodsThe Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE, CINAHL, and AMED were searched for published resultsalong with trial registries and the Journal of Negative Results in BioMedicine for grey literature. The date of the most recent search wasJuly 2015.Selection criteriaRandomised controlled trials (RCTs) comparing OIT or SLIT with placebo or an elimination diet were included. Participants were childrenor adults diagnosed with food allergy who presented immediate fruit reactions.Data collection and analysisWe used standard methodological procedures expected by the Cochrane Collaboration. We assessed treatment effect through risk ratios(RRs) for dichotomous outcomes. Main resultsWe identified two RCTs (N=89) eligible for inclusion. These RCTs addressed oral or sublingual immunotherapy, both in adults, with an allergyto apple or peach respectively. Both studies enrolled a small number of participants and used different methods to provide these differingtypes of immunotherapy. Both studies were judged to be at high risk of bias in at least one domain. Overall, the quality of evidence wasjudged to be very low due to the small number of studies and participants and possible bias. The studies were clinically heterogeneous andhence we did not pool the results. A study comparing SLIT with placebo for allergy to peach did not detect a significant difference betweenthe number of patients desensitised at six months following a double-blind placebo-controlled food challenge (RR 1.16, 95% confidenceinterval (CI) 0.49 to 2.74). The second study, comparing OIT versus no treatment for apple allergy, found an effect on desensitisation infavour of the intervention using an oral provocation test at eight months, but results were imprecise (RR 17.50, 95% CI 1.13 to 270.19).Neither study reported data on evidence of immunologic tolerance. In both studies, the incidence of mild and moderate adverse eventswas higher in the intervention groups than in the controls. In the study comparing SLIT with placebo, patients in the intervention groupexperienced significantly more local adverse reactions than participants in the control group (RR 3.21, 95% CI 1.51 to 6.82), though therewas not a significant difference in the number of participants experiencing systemic adverse reactions (RR 0.81, 95% CI 0.22 to 3.02). Inthe study of OIT, two of the 25 participants in the intervention group reported relevant side effects, whereas no participants in the controlgroup reported relevant side effects.